O miniconto multimodal: potencialidades do gênero para uma prática transformadora no ensino fundamental - Santos, Marlene Santana dos (2024)
The changes in the field of languages, which also result from the social practices of virtual and face-to-face interaction, are present in various contexts, giving rise to new textual genres due to the needs of current discursive practices. Discussing the concepts of discursive genres (Bakhtin, 2003), language genres (Larsen-Freeman; Cameron, 2008 and Paiva, 2019), and multimodality (Rojo; Moura, 2012) contributes to the understanding of these emerging textual genres, such as the case of multimodal micro stories discussed here as mediators of reading development in basic education. Addressing the current panorama of digital practices in light of the implications of the lack of reading competence in students in the final grades of elementary school is a significant challenge and, therefore, is the aim of this research. This action research presents a didactic-pedagogical approach with multimodal micro stories motivated through Marina Colasanti's peculiar writing (2010 [1986]), the mini-fiction, under the lens of the nuances that the female figure faces in current life, to contribute to the promotion of students' reading proficiency and critical literacy. It extends the development of discursive practices and social transformation based on the theoretical foundations of Fairclough (2001) and Paulo Freire (1991). Furthermore, Candido (2004) and Cosson (2014) justify literary reading practice for the understanding of the real world. Kleiman (2009), Lopes-Rossi (2005), Solé (1998), and other contributors bring pedagogical actions of reading and writing and approaches with the aforementioned genre. Anchored in the methodological assumptions of action research, with the contribution of Bortoni-Ricardo (2008) and David Tripp (2005), this research was developed in a 9th-grade class of a public school located in Paripiranga City, in the State of Bahia, Brazil. The methodological intervention path was carried out through the application of the Mini stories Didactic Sequence in life: reflecting and transforming, which resulted in a Workbook. The reading diagnosis and the application of the pedagogical proposal brought results and perspectives, such as emancipatory reading practices and reading and writing practices that allowed new perspectives of social change alongside the protagonism and representation of the female figure.